From dry-land to the water: training and testing practices of strength and conditioning coaches in high level French sprint swimmers - Raineteau, Y.; Pla, R.; Bideau, B.; Bideau, N.; Nicolas, G. (Frontiers in Physiology, 2023)
Introduction The aim of this study was to explore training and testing practices from Strength & Conditioning (S&C) coaches who manage groups of high-level French swimmers in elite training centers. The transfer of abilities from dry-land to in situ condition was also investigated.